Genetic similarities and differences between discoid and systemic lupus erythematosus patients within the Polish population - Skonieczna, Katarzyna; Czajkowski, Rafał; Kaszewski, Sebastian; Gawrych, Mariusz; Jakubowska, Aneta; Grzybowski, Tomasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Many studies have shown that some SNPs might be a risk factor for systemic lupus erythematosus (SLE), but little is known about potential susceptibility loci of the skin types of the disease. Discoid lupus erythematosus (DLE) is the most common form of the cutaneous lupus erythematosus. Nevertheless, a genetic contribution to DLE is not fully recognized. Aim: We aimed to analyze three SNPs located in the STAT4 (rs7574865), ITGAM (rs1143679) and TNXB (rs1150754) genes in both DLE and SLE patients from Poland. Material and methods: SNPs were genotyped using real-time polymerase chain reaction (PCR). Statistical significance of the differences between patient and control groups in both allele and genotype frequencies were calculated using two tailed Fisher’s exact test. The correction for multiple testing by the Bonferroni adjustment and odds ratio were also calculated. Results : For the first time, we have shown that the polymorphisms located in the STAT4 (rs7574865), but not in the ITGAM (rs1143679) nor the TNXB (rs1150754) genes, might be associated with the development of DLE within the Polish population. The variation of the three investigated SNPs was found to be associated with SLE in our dataset. Conclusions : The results of our study suggest differences in the molecular background between DLE and SLE within the Polish population.